An Empirical Investigation of U.S. Firms in Reorganization - FRANKS, JULIAN R.; TOROUS, WALTER N. (Journal of Finance, 1989)
ABSTRACT The purpose of this paper is to understand the institutional features of Chapter 11 from an empirical examination of thirty firms that have emerged from reorganization. We find the recontracting framework of Chapter 11 to be complex, lengthy, and costly. Violations of absolute priority in favor of stockholders are frequently encountered. These deviations may result from the bargaining process of Chapter 11 or from a recontracting process between creditors and stockholders which recognizes the ability of stockholder‐oriented management to preserve firm value. An example of such recontracting addresses Myers' underinvestment problem. An investigation of the effects of Chapter 11 on the pricing of risky debt is also provided.